Manajemen Keungan Digital - Sri Puspita Sari; Anjely Shukriya Aini; Anwar Sanusi; Jasica Asih Hati; Muhammad Adam; Nani Qurotul A’yun; Masno Marjohan (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
The rapid development of digital technology has brought a revolutionary impact on almost every aspect of life, including finance. Digital financial management is not just about using financial applications or accounting software, digital financial management offers various advantages, this transformation also presents major challenges. The method used in this research activity uses a qualitative approach method where this approach explores and understands the meaning of some individuals or groups of people who come from social problems. The scope of digital financial management is the entire financial management activity that involves the use of information technology as the main tool in the process of planning, budgeting, reporting, auditing, and financial decision making. The scope of digital financial management is the entire financial management activity that involves the use of information technology as the main tool in the process of planning, budgeting, reporting, auditing, and financial decision making. Digital financial management has been widely implemented in various sectors, both public and private, with varying results. Digital financial management is a fundamental transformation in financial management driven by the development of digital technology. This transformation offers various benefits, such as increased efficiency, transparency, accountability, and better decision making. However, its implementation also faces various challenges and obstacles that need to be overcome.